Evaluation of the effects of different supplementation on oxidative status in patients with rheumatoid arthritis. Issue 8 (August 2016) - Vasiljevic, Dragan; Veselinovic, Mirjana; Jovanovic, Maja; Jeremic, Nevena; Arsic, Aleksandra; Vucic, Vesna; Lucic-Tomic, Aleksandra; Zivanovic, Sandra; Djuric, Dragan; Jakovljevic, Vladimir
Abstract Rheumatoid arthritis is a chronic inflammatory disease. Reactive oxygen species have been considered as aggravating factors for autoimmune diseases. Fatty acids had been linked in reduction of various diseases by augment of their antioxidant potential and antiinflammatory mechanisms. The aim of this study was to assess the oxidative status in patients with rheumatoid arthritis who used concentrated fish oil only or concentrated fish oil in combination with evening primrose oil in a period of 3 months. Subjects were divided into three groups. The group I consists of patients who had been taking only their regular rheumatologic therapy; group II, patients who had been taking concentrated fish oil; and group III, patients who had been taking concentrated fish oil and evening primrose oil. Peripheral blood samples were used for all the assays. We assessed the following oxidative stress markers: index of lipid peroxidation (thiobarbituric acid-reactive substances (TBARS)), hydrogen peroxide (H2 O2 ), superoxide anion radical (O2 − ), nitric oxide (NO), superoxide dismutase activity (SOD), catalase activity (CAT), and glutathione levels (GSH) in erythrocytes. There were no statistically significant changes for any of the oxidative stress parameters in group I. In group II, levels of TBARS, NO2 −, and GSH were increased, while levels of H2 O2 decreased. Increased values of TBARS, NO2 −, and SOD were found in group III. Our findings indicate that intakes of fish oil and evening primrose oil may be of importance in mitigation of inflammation, disease activity, and oxidative stress biomarkers, through increased activities of antioxidant enzymes.